Outcomes from a multimodal, at‐scale community‐based HIV counselling and testing programme in twelve high HIV burden districts in South Africa. Issue 3 (11th March 2021) - Medina‐Marino, Andrew; Daniels, Joseph; Bezuidenhout, Dana; Peters, Remco; Farirai, Thato; Slabbert, Jean; Guloba, Geoffrey; Johnson, Suzanne; Bekker, Linda‐Gail; Nkhwashu, Nkhensani
Abstract: Introduction: Facility‐based HIV testing services (HTS) have been less acceptable and accessible by adolescents, men and key populations in South Africa. Community‐based HIV counselling and testing (CBCT) modalities, including mobile unit and home‐based testing, have been proposed to decrease barriers to HIV testing uptake. CBCT modalities and approaches may be differentially acceptable to men and women based on age. Implementation of multimodal CBCT services may improve HIV testing rates among adolescents and men, and support the roll‐out of prevention services. Methods: A cross‐sectional analysis was conducted using aggregate, routine programmatic data collected from 1 October 2015 through 31 March 2017 from a multimodal, at‐scale CBCT programme implemented in 12 high‐burden districts throughout South Africa. Data collection tools were aligned to reporting standards for the National Department of Health and donor requirements. HIV testing rates (i.e. number of tests performed per 100, 000 population using South African census data) and testing proportions by modality were stratified by sex, age groups and heath districts. Descriptive statistics were performed using STATA 13.0. Results: Overall, 944, 487 tests were performed during the 1.5‐year testing period reported. More tests were conducted among females than males (53.6% vs. 46.4%). Overall, 8206 tests per 100, 000 population (95% CI: 8190.2 to 8221.9) were performed; female‐to‐male (F:M) testing ratio was 1.11. Testing rates were highest among young women age 20 to 24 years (16, 328.4; 95% CI: 16, 237.9 to 16, 419.1) and adolescent girls aged 15 to 19 years (12, 817.0; 95% CI: 12, 727.9 to 12, 906.6). Home‐based testing accounted for 61.3% of HIV tests, followed by near‐home mobile unit testing (30.2%) and workplace mobile unit testing (4.7%). More women received HTS via home‐based testing (F:M ratio = 1.29), whereas more men accessed work‐place mobile testing (M:F ratio = 1.35). No sex differential was observed among those accessing near‐home mobile testing (F:M ratio = 0.98). Conclusions: Concurrent implementation of multiple, targeted CBCT modalities can reduce sex disparities in HIV testing in South Africa. Given the acceptability and accessibility of these CBCT services to adolescent girls and young women, evident from their high testing rates, leveraging community‐based services delivery platforms to increase access to HIV prevention services, including pre‐exposure prophylaxis (PrEP), should be considered.